Unipolar hip prosthesis with nanocomposite ceramic coated femoral head - Zykova, Anna; Safonov, Vladimir; Lukyanchenko, Volodimir; Samoilenko, Olexsandr; Rogowska, Renata; Smolik, Jerzy; Donkov, Nikolai (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Hip arthroplasty in elderly patients is the most progressive method of medical treatment. The method provides rapid recovery and rehabilitation of musculoskeletal systems at an earlier period. The aim of the present study was to analyze the structural and mechanical properties of unipolar prosthesis head surfaces made of titanium and stainless steel and coated by oxide and oxynitride nanocomposite for hemiarthroplastic hip replacement as well as clinical approbation of prostheses «BES-T Manufacturing» (Ukraine), for possibility of applying this technology in traumatology. The structure of Al2O3 (MS) and AlN/ Al2O3 (MS) magnetron sputtered films was investigated by means of XPS and XRD methods. The surface topography and roughness was estimated by profilometer Hommel T-2000 measurements and by AFM method. ElvaX spectrometer is modern analytical equipment for high-line non-destructive elemental analysis. The analysis of the results of treatment patient’s with fractures of the femoral neck under observation period from 12 months to 3 years was presented. The unipolar hip replacement operations were made in urban trauma hospital during the period from 2012 to 2014. The age of patients was in the range from 72 to 86 years. All patients had a history of intra-articular fractures of the femoral neck. The joint femoral head surfaces with nanocomposite oxide and oxinitride coatings demonstrate improved biocompatibility due to wettability increasing and fluid friction characteristics advancing. The deep understanding of the tribology of artificial joints is essential for reducing wear and corrosion of modern prostheses. Deposition of ceramic coatings on a surface of metal artificial joint’s head is an effective way to advance the functional characteristics of unipolar and bipolar prosthesis for joint arthroplasty.